Parrot in the oven : mi vida : a novel - Martinez, Victor (New York : HarperCollins Publishers, 1996)
Manny relates his coming of age experiences as a member of a poor Mexican American family in which the alcoholic father only adds to everyone's struggle.
Keywords: Family life